Serve the people : ang kasaysayan ng radikal na kilusan sa Unibersidad ng Pilipinas - 4 0 16; Lumbera, Bienvenido; 5 (Quezon City, Philippines : Ibon Books, 2008)
Collection of stories on activism and radical movements within the premier state university in the Philippines.
Includes bibliographical references.
In Tagalog and some articles in English.
Keywords: 2 -- 0; Students;Political activity. -- University of the Philippines -- 6; History.;Students;Political activity.;Political activity. -- Student movements;Radicalism;University of the Philippines;Students -- Philippines.;Philippines;Philippines; 20; 2